Analisis Farmakoekonomi Terhadap Regimen Kemoterapi Pasien Kanker Payudara Di Rumah Sakit Universitas Hasanuddin Makassar - yuliana, Dewi; Fairuz Dyah Widowati; Muammar Fawwaz (Jurusan Farmasi Poltekkes kemenkes Makassar, 2024)
Therapy given to breast cancer patients is usually carried out in several cycles, while the cost of treatment increases every year, so this situation can become an economic burden for breast cancer sufferers. Therefore, to reduce the cost burden for sufferers, it is necessary to know which therapy is cost-effective and therapy with a pharmacoeconomic approach, namely using cost-effectiveness analysis. The purpose of the analysis is to determine the cost effectiveness and cost utility of the treatment regimen for breast cancer chemotherapy patients at the Makassar Unhas Hospital. This research is a descriptive study with a retrospective approach, data was taken from patient medical records and patient administration. The sampling technique was purposive sampling with a diagnosis of breast cancer at Makassar Unhas Hospital in 2023 and a total sample of 60 patients. The data analysis method uses cost-effective. Based on the results and discussions that have been carried out in this research, it was concluded that the cost effectiveness of the treatment regimen for breast cancer patients at Makassar Unhas Hospital for the 2023 period in patients using the combination chemotherapy drug Paclitaxel+Epirubicin+Cyclophosphamide is more cost-effective with the Average Cost Effectiveness Ratio value (ACER) with a cost of IDR 80,819 and the Incremental Cost Effectiveness Ratio (ICER) for therapy using Paclitaxel+Epirubicin+Cyclophosphamide is more cost effective than Fluronacil+Epirubicin +Cyclophosphamide with a value of IDR 83,651. The utility costs of treatment regimens for breast cancer patients at Makassar Unhas Hospital for the 2023 period, in patients with utility analysis obtained from the QALYS value in patients using the breast cancer chemotherapy drug combination Paclitaxel+Epirubicin+Cycphosphamide is 40,638 and CUA IDR 325,629 compared to those using Fluronacil+ Epirubicin+Cyclophosphamide. Terapi yang diberikan kepada pasien kanker payudara biasanya dilakukan dalam beberapa siklus, sedangkan biaya pengobatan semakin meningkat setiap tahunnya, sehingga keadaan tersebut dapat menjadi beban ekonomi bagi para penderita kanker payudara. Oleh karena itu untuk mengurangi beban biaya bagi penderita maka perlu dilakukan kajian terapi yang efektif secara biaya dan terapi dengan pendekatan farmakoekonomi yaitu menggunakan cost effectiveness analysis (analisis efektivitas biaya) dan utilitas biaya. Tujuan analisis ialah untuk mengetahui efektifitas biaya dan utilitas biaya regimen pengobatan pasien kemoterapi kanker payudara di Rumah Sakit Unhas Makassar. Penelitian ini merupakan penelitian deskriptif dengan pendekatan retrospektif, data diambil dari rekam medis pasien dan administrasi pasien. Teknik sampling ialah purposive sampling dengan diagnosa kanker payudara di Rumah Sakit Unhas Makassar tahun 2023 dan jumlah sampel sebanyak 60 Pasien. Efektivitas biaya regimen pengobatan pasien kanker payudara di Rumah Sakit Unhas Makassar Periode 2023 pada pasien yang menggunakan obat kemoterapi kombinasi Paclitaxel+Epirubicin+Cyclophosphamide adalah memiliki biaya efektifitas yang lebih dengan nilai Average Cost Effectiveness Ratio (ACER) dengan biaya sebanyak Rp80.819 dan Inceremental Cost Effectiveness Ratio (ICER) untuk terapi dengan menggunakan Paclitaxel+Epirubicin+Cyclophosphamide lebih cost efektif dibandingkan Fluronacil+Epirubicin +Cyclophosphamide dengan nilai Rp 83.651. Utilitas biaya regimen pengobatan pasien kanker payudara di Rumah Sakit Unhas Makassar Periode 2023, pada pasien dengan analisis utilitas yang diperoleh dari nilai QALYS pada pasien yang menggunakan kombinasi obat kemoterapi kanker payudara Paclitaxel+Epirubicin+Cyclophosphamide sebesarr 40,638 dan CUA Rp 325.629 dibandingkan dengan yang menggunakan Fluronacil+Epirubicin+Cyclophosphamide.